Бесфонная гетерогенная рекомбинация атомов на поверхности порошков - Васильев А. А. Анатолий Анатольевич; Лисецкий В. Н. Владимир Николаевич; Савельев Г. Г. Геннадий Гаврилович; Ковалев Д. В. Дмитрий Владимирович (1986, 1986)
Деп. в ОНИИТЭХим г. Черкассы 01.10.86, № 1163-ХП-86.